Uji aktivitas antimikroba ekstrak daun tumbuhan akar kucing (Acalypha indica l.) terhadap mikroba patogen manusia - M. Guli, Musjaya; Darmiyati; Ardiputra, Muh.Akbar; Toemon, Agnes Immanuela (Jurnal Kedokteran Universitas Palangka Raya, 2023)
The leaves of Acalypha indica L. were used as the object that are easily found around the home contain secondary metabolites as antimicrobials for Meticillin Resistant Staphylococcus aureus (MRSA) and Candida albicans. The method used for plant sampling is purposive sampling method. Extraction of active compounds using maceration method. The antimicrobial potency test used the agar-diffusion method using two types of microbial pathogens: Meticillin Resistant Staphylococcus aureus (MRSA) and C. albicans. Each paper disk was given 50 L of bacterial isolate and incubated at 370 C for 24 hours and continued for 48 hours. The parameter observed is the clear zone formed around the paper disk. The results showed that the leaves of contained compounds that could inhibit the growth of MRSA bacteria and the fungus. A good solvent to extract the active compounds contained in the leaves of is distilled water. The extract - distilled water treatment with a concentration of 100% had the widest inhibition zone among other treatments, which was 4.5 mm against the growth of the fungus